The valley Nernst effect in WSe2 - Minh Tuan Dau (Nature Portfolio, 2019)
Atomically thin transition metal dichalcogenides possess a valley degree of freedom, which could enrich the physics underpinning the conventional Nernst effect observed in traditional solids. Here, the authors report experimental evidence of the valley Nernst effect in WSe2 at room temperature.